Wielki koncert. ([S.l. : s.n.], 1946)
Afisz inf. o koncercie, który miał miejsce w Hali kadłubowni w Stoczni nr. 1 w Gdańsku 14.09.1946 r.
Keywords: Życie artystyczne -- Polska -- Gdańsk -- 1945-1970.; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- plakaty